Assessing a partnership-based model of surgical education in the Global South: a mixed methods study of the University of Global Health Equity, Rwanda - Naol Belema Gemechu; Gatwiri Murithi; Derbew Fikadu Berhe; Betel Amdeslassie Fenta; Amanuel Adane Bitew; Tairu Fofanah; Barnabas Tobi Alayande; Abebe Bekele; Geoffrey Anderson; Robert Riviello (BMC Surgery)
Abstract Background Workforce shortages, resource limitations, and inadequate capacity in African higher education institutions are significant challenges that hinder their global competitiveness in generating knowledge products. Academic partnerships have been established to address these gaps. It is essential to evaluate these partnerships to ensure they align with principles of ethics, equity, reciprocity, and the achievement of shared goals. The University of Global Health Equity (UGHE) is an institution that employs a partnership-based model to deliver high-quality surgical education. The aim of the study was to assess its partnership based surgical education programs. Methods This study was conducted at UGHE using a sequential exploratory mixed-methods design that incorporates perspectives of learners, facility and partners. Qualitative interviews were conducted with students, faculty, and partners involved in UGHE’s surgical education programs within the last three years. Thematic analysis was employed to interpret the interview data. Quantitative data were summarized using descriptive statistics and presented in charts and tables with integration in a joint display. Results Twenty-one interviews were conducted, revealing 4 key themes from the thematic analysis: (1) A needs-based approach is used to determine the suitability of partnerships (2), UGHE and its partners worked towards equitable outcomes (3), Positive outcomes of the partnership model (4) Challenges faced in delivering surgical education using a partnership model and proposed solutions. Most participants viewed the model positively, identifying benefits such as diverse exposure, improved student experiences, faculty development, and technology transfer. However, institutional and systemic gaps that limit maximum benefits were noted. The quantitative survey had a 42% response rate with 31 responses from undergraduate and postgraduate students. All students agreed that didactic and simulation sessions led by UGHE partners enhanced their learning. A significant difference (p <.001) was found between postgraduate and undergraduate students’ responses regarding the adequacy of time for partner-facilitated sessions. Conclusions The results underscore the significant positive impact of UGHE’s institutional partnership-based model in delivering surgical education, especially in enhancing student learning and faculty capacity. However, communication gaps, lack of resources, and time prevent the partnership-based model from reaching full potential.